A facile evanescent-field imaging approach for monitoring colloidal gel evolution near a surface. Issue 15 (12th April 2021) - Liu, Wei; Wu, Jiahao; Zhu, Hui; He, Chuanxin; Ngai, To
Abstract : A facile evanescent-field imaging approach is developed to probe the aggregation behavior of near-wall colloids/clusters during colloidal gel evolution. Abstract : A facile evanescent-field imaging approach is developed to probe the aggregation behavior of near-wall colloids/clusters during colloidal gel evolution. Total internal reflection microscope (TIRM) images are directly utilized to access the structural relaxation time via density-fluctuation theory. The behaviors of cluster–cluster aggregation and physical aging of the colloidal gel networks are resolved in both time and space under fractal scaling criteria.